(untitled) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2021)
The spread of the Covid-19 virus, which caused a pandemic, has affected various aspects of life, including the educational world. Through Circular Letter Number 4 of 2020, the Ministry of Education and Culture regarding the implementation of education policies in the emergency period of the spread of the coronavirus disease (Covid-19). Requires all learning activities to be carried out online or better known as Pembelajaran Jarak Jauh (PJJ). No exception for SMA Negeri 7 Bandung, which carries out online learning. Implementing Pembelajaran Jarak Jauh (PJJ) is new for most schools; thus, many challenges need to be overcome. One of the media commonly used in this school is Zoom Meeting. This study discusses the activeness of students in online history learning through Zoom Meetings. The research method used is a descriptive study. This study indicates that various factors influence students’ activeness, and each individual has a distinct factor, both from within and outside influences. The role of the teacher is also crucial in developing activeness and optimizing learning amid a pandemic. The activeness of students depicted through this research included giving an opinion, responding, and asking questions. However, the activeness of students in learning history using Zoom Meeting is still not optimal, so there needs to be good cooperation and coordination between teachers and students.